A new anti-inflammatory flavonoid glycoside from tetraena aegyptia. Issue 12 (31st May 2021) - Zaki, Ahmed A.; Xu, Xiaoqian; Wang, Yuewen; Shie, Pei-Hsin; Qiu, Longxin
Abstract: The chromatographic reinvestigation the methanol extract of Tetraena aegyptia led to the separation of a new flavonoid glycoside, isorhamnetin-3- O -[2```, 3```- O -isopropylidene-α-L-rhamnopyranosyl]-(1```→6``)- O -β-D-glucopyranoside (1 ), together with two known flavonoids, isorhamnetin (2 ) and isorhamnetin-3- O -glucoside (3 ), isolated for the first time from the plant. The new compound was evaluated for the anti-inflammatory activity by using LPS-induce RAW 264.7 cells model. Compound 1 showed significant inhibitory effect on NO release. ELISA assay showed a pronounced effect of 1 on the secretion of cytokines IL-6 and TNF-α, in a dose-dependent manner. Consistent results were obtained by qRT-PCR which revealed that compound 1 markedly reduced the mRNA expression of IL-6 and TNF-α. Together these data, we demonstrated the anti-inflammatory activity of compound 1 . Graphical Abstract: